Analysis of Cyber Attacks on Network Security - Fauzan Prasetyo Eka Putra; Ubaidi; Anggreni Amba Sugi, Senah; Khafifatul Mufidah; Yayu Rahma Febriani (Jurnal Informasi dan Teknologi, 2024)
Network security is a crucial issue in today's digital era, with increasing cyber attacks targeting infrastructure and sensitive data. Analysis of cyber attacks on network security is an important aspect of efforts to protect information systems from ever-evolving digital threats. This research investigates various types of cyberattacks that can threaten network security, including phishing attacks, malware, denial of service (DoS), and brute force attacks. We also analyze defense methods that can be used to reduce the risk of cyberattacks, including firewalls, data encryption, real-time security monitoring, and security training for users. This research provides a deeper understanding of the current cyberattack landscape and effective strategies for reducing network vulnerabilities to such attacks. Thus, the results of this analysis can make an important contribution to improving network security in various sectors, from companies to government.